Influence of program of prophylaxis of violations of vaults of foot on sagital type of foot of junior school age children. - Valcevich A.V; Bychuk A.I (Kharkov National Pedagogical University, 2012)
Purpose of work - to analyse influence of the program of prophylaxis of violation of vaults of foot of junior schoolchildren on biomechanics descriptions of foot. 40 children who studied in a tourist class took part in an experiment. All of children on the state a health were attributed to the basic group. Linear and angular biomechanics descriptions of foot of children are certain. A dynamics and increase of the probed indexes is analysed during realization of the program of prophylaxis of violation of vaults of foot in the educational process of schoolboys. Directions organization of correct training conditions of students in part of dosage of the physical loadings is shown. Implementation of the program of prophylaxis phases is recommended. It is marked that in realization of the program must take part teachers of physical culture and parents.